The cost of behavioral and psychological symptoms of dementia (BPSD) in community dwelling Alzheimer's disease patients. - Beeri, MS; Werner, P; Davidson, M; Noy, S (2002)
INTRODUCTION: Behavioral and psychological symptoms of dementia (BPSD) are highly prevalent in Alzheimer's disease (AD) patients. They are a source of distress for the caregivers and one of the main reasons for nursing home placement, which is the major component of the cost of Alzheimer's disease. The aim of the present study was to assess the direct and indirect cost related to the care of BPSD within a prospective study examining the overall cost of AD in Israel. METHODS: Seventy-one community dwelling AD patients were interviewed. Interviews covered information about the number of caregivers' hours invested in caring for the patient and amount of expenditure such as in-house paid help and payments for day care. Effort devoted to BPSD was defined as the number of hours spent by primary and secondary caregivers in a typical week dealing with BPSD (managing aggression, pacing, attempts to leave the house under inappropriate circumstances, or comforting a hallucinating, depressed or anxious patient). RESULTS: The annual indirect cost for management of BPSD in an AD patient was approximately 2665 dollars -over 25% of the total annual indirect cost of care ($10 520). The annual direct cost of BPSD of an AD patient was approximately 1450 dollars -over 35% of the total annual direct cost of care (3900 dollars). CONCLUSIONS: Approximately 30% (4115 dollars) of the total annual cost of AD (14420 dollars) is invested in the direct management of BPSD. Given the importance of BPSD as one of the main components of the cost of AD, future cost studies should be designed to measure the cost of specific components of BPSD and verify which are the most costly aspects of the disease. Despite the considerable methodological difficulties in disentangling the costs of the specific symptoms of AD, cost effectiveness studies of different interventions should be conducted in order to determine the optimal intervention with relation to cost.